Connected Soldiers : Life, Leadership, and Social Connections in Modern War - Spencer, John, 1975- (Book collections on Project MUSE., 2022)
"Connected Soldiers recounts the action sequences that made the author a great combat leader, the methods he used to build unit cohesion, and then how he supported his wife as a stay at home father when his wife went off to war"--